JRHM 2021
DOI: 10.25259/jrhm_31_2020
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological outcomes of uterine niche after cesarean section: A descriptive study

Abstract: Objectives: Our aim was to study the prevalence of isthmocele in cases with previous cesarean section scar presented to El Shatby maternity university hospital and its association with gynecological complications. Material and Methods: After approval of the ethics committee of Alexandria faculty of medicine, a sample of 300 patients delivered by cesarean section since 6 months or more presented by one or more of the following symptoms: Abnormal uterine bleeding (AUB) dysmenorrhea, secondary infertility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Regarding gynaecological symptoms, this study shows that more than half of women with CSN were symptomatic, which was also reported by Abdelfattah et al and the other studies mentioned below (7) .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding gynaecological symptoms, this study shows that more than half of women with CSN were symptomatic, which was also reported by Abdelfattah et al and the other studies mentioned below (7) .…”
Section: Discussionsupporting
confidence: 87%
“…In this study, niche was present in 44% of cases, which goes with the study done by Gozzi et al, who detected a prevalence of niche of 44.4% (8) . It is near to a systematic review done by Bij de Vaat et al, who found a prevalence of 24-70% when detected by TVU and between 56% and 84% when detected by SHG from twenty-one paper s (4) , and studies done by Abd (,9,10,13,14) , but does not agree with Osser et al which showed 70% detection by TVU and 84% detection by SHG (11) , and a study done by Abdelfattah et al which shows niche in 14.7% of cases detected by TVU, these may be related to the different procedure of CS, different study population, different criteria, and detection of niche by different personnel (7) .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Based on parity, 194 (64.67%) patients had parity 1-2, 102 (34.00%) patients had parity 3-4, and 4 (1.33%) patients had parity >5. For history of CS, 115 (38.33%) patients had only one history of previous CS, 116 (38.67%) patients had history of two previous CS, 67 (23.33%) patients had history of three previous CS, and 2 (0.67%) patients had history of four previous CS [22].…”
Section: Discussionmentioning
confidence: 99%